Air dispersion modeling : foundations and applications - De Visscher, Alex, 1970- (Hoboken, NJ : A John Wiley & Sons, Inc., Publication, 2013)
'Air dispersion models are used by many industries for the design of effective control strategies to reduce emissions of harmful air pollutants. Providing the underlying science for formulating air dispersion models, this innovate text introduces the fundamentals, discusses implementation issues of air dispersion models, and provides a detailed description of the most widely used air dispersion models. Air Dispersion Modeling provides researchers, professionals, and graduate students with all the background information they need to use air dispersion models with confidence'--
Machine generated contents note: Preface List of Symbols Chapter 1 Introduction 1.1 Introduction 1.2 Types of Air Dispersion Models 1.3 Standard Conditions for Temperature and Pressure 1.4 Concentration Units in the Gas Phase 1.5 Units 1.6 Constants and Approximately Constant Variables 1.7 Frequently Used Greek Symbols 1.8 Problems 1.9 References Chapter 2 An Air Dispersion Modeling Primer 2.1 Introduction 2.2 The Basic Concepts of Air Dispersion 2.3 The Gaussian Dispersion Model 2.4 Plume Rise 2.5 Needs for Refinements to the Basic Gaussian Plume Dispersion Model 2.6 Problems 2.7 Materials in CD 2.8 References Chapter 3 Air Pollutants - An Overview 3.1 Introduction 3.2 Types of Air Pollution 3.3 Problems 3.4 References Chapter 4 Regulation of Air Quality and Air Quality Modeling 4.1 Introduction 4.2 Air Quality Regulation 4.3 Air Dispersion Modeling Guidelines 4.4 References Chapter 5 Meteorology for Air Dispersion Modelers 5.1 Introduction 5.2 The Structure of the Atmosphere 5.3 Altitude Dependence of Barometric Pressure 5.4 Height Dependence of Temperature - Adiabatic Case 5.5 Stability 5.6 The Heat Balance 5.7 The Wind Speed Profile 5.8 Temperature Profile Revisited - Non-Neutral Conditions 5.9 The Heat Balance Revisited: Stable Conditions 5.10 The Mixing Layer Height 5.11 The Concept of Turbulence 5.12 Special Topics in Meteorology 5.13 Advanced Topics in Meteorology 5.14 Summary of the Main Equations 5 15 Problems 5.16 Materials on CD 5.17 References Chapter 6 Gaussian Dispersion Modeling: An In-Depth Study 6.1 Introduction 6.2 Gaussian Plume Models 6.3 Parameterizations Based on Stability Classes 6.4 A Gaussian Plume Dispersion Short Cut 6.5 Plume Dispersion Modifiers 6.6 Continuous Parameterization for Gaussian Dispersion Models 6.7 Gaussian Plume Models for Non-Point Sources 6.8 The Virtual Source Concept 6.9 Special Issues 6.10 Gaussian Puff Modeling 6.11 Advanced Topics in Meteorology 6.12 Summary of the Main Equations 6.13 Problems 6.14 Materials on CD 6.15 References Chapter 7 Plume-Atmosphere Interactions 7.1 Introduction 7.2 Plume Rise 7.3 Plume Downwash: PRIME (Plume RIse Model Enhancements) 7.4 Behavior of Denser-Than-Air Plumes 7.5 Deposition 7.6 Summary of the Main Equations 7.7 Problems 7.8 Materials on CD 7.9 References Chapter 8 Gaussian Model Approaches in Urban or Industrial Terrain 8.1 Introduction 8.2 Wind Flow around Obstacles 8.3 Surface Roughness and Displacement Height in Urban and Industrial Terrain 8.4 Wind Speed Profiles near the Surface: Deviations from Similarity Theory 8.5 Turbulence in Urban Terrain 8.6 Dispersion Calculations in Urban Terrain near the Surface 8.7 An Example 8.8 Summary of the Main Equations 8.9 Problems 8.10 Materials on CD 8.11 References Chapter 9 Stochastic Modeling Approaches 9.1 Introduction 9.2 Fundamentals of Stochastic Air Dispersion Modeling 9.3 Numerical Aspects of Stochastic Modeling 9.4 Stochastic Lagrangian Calculation Examples 9.5 Summary of the Main Equations 9.6 Problems 9.7 Materials on CD 9.8 References Chapter 10 Computational Fluid Dynamics and Meteorological Modeling 10.1 Introduction 10.2 CFD Model Formulation: Fundamentals 10.3 Reynolds Averaged Navier-Stokes (RANS) Techniques 10.4 Large Eddy Simulation (LAS) 10.5 Numerical Methods in CFD 10.6 Meteorological Modeling 10.7 Summary of the Main Equations 10.8 References Chapter 11 Eulerian Model Approaches 11.1 Introduction 11.2 Governing Equations of Eulerian Dispersion Models 11.3 Closing the Material Balance for Turbulent Motion 11.4 Atmospheric Chemistry 11.5 Numerical Aspects of Eulerian Dispersion Modeling 11.6 Summary of the Main Equations 11.7 Problems 11.8 References Chapter 12 Practical Aspects of Air Dispersion Modeling 12.1 Introcuction 12.2 Source Characterization and Source Modeling 12.3 Coordinate Systems 12.4 Data Handling 12.5 Model Validation 12.6 References Chapter 13 ISC3 and SCREEN3: A Detailed Description 13.1 Introduction 13.2 ISC3 Model Description 13.3 SCREEN3 Model Description 13.4 References Chapter 14 AERMOD and AERMET: A Detailed Description 14.1 Introduction 14.2 Description of AERMET 14.3 Description of AERMOD 14.4 References Chapter 15 CALPUFF and CALMET: A Detailed Description 15.1 Introduction 15.2 Description of CALMET 15.3 Description of CALPUFF 15.4 References Chapter 16 CMAQ: A Brief Description 16.1 Introduction 16.2 Main Features of CMAQ 16.3 Advection and Diffusion Modeling in CMAQ 16.4 Atmospheric Chemistry Modeling in CMAQ 16.5 References Appendix A Auxiliary Calculations and Derivations Appendix B Auxiliary Data and Methods Appendix C A Theory of Near Surface Turbulence Applied to Wind Speed Profiles, Dry Deposition, Air-Water Exchange and Canopy Effects Index .
Includes bibliographical references and index.
Keywords: Air -- Pollution -- Simulation methods; Atmospheric diffusion -- Simulation methods